EFEKTIVITAS TERAPI TOUCH AND TALK DAN TERAPI BERCERITA TERHADAP KECEMASAN ANAK USIA 3-6 TAHUN DI RUANG EDELWEIYS RSUD Dr. M. YUNUS BENGKULU - Harsismanto J Harsismanto J; Lussyefrida Yanti; Ilham Alfathona (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Between preschool age children will be very careful about something that is considered hurt themselves, besides that children's fears can occur because children are afraid of losing parents like when children are treated. The purpose of this study was to determine the comparison of the effectiveness of touch and talk therapy and therapy storytelling to anxiety of children aged 3-6 years in Edelweis rooms RSUD Dr. M. Yunus Bengkulu.This research is a quantitative study with a quasy experiment design, two groups pretest-posttest design. Sample of 32 respondents was taken by purposive sampling technique which was divided into 2 intervention groups. The results were obtained from 16 respondents before Touch and talk therapy. The average anxiety score was 31.62 and after intervention was 17.31 with a p-value of 0.000, the therapy group storytelling from 16 respondents, the average anxiety score before giving intervention was 31.56 and after intervention was 24.38 with p-value 0,000.The results of the statistical test scores after touch and talk therapy and storytelling therapy obtained p-value 0.001 <alpha (0.05). It can be concluded that there are differences in effectiveness between touch and talk therapy and storytelling therapy. Touch and talk therapy is more significant for reducing anxiety in children aged 3-6 years compared to storytelling therapy. Further research is suggested to be able to collaborate between these two therapies with other therapies by considering the factors that influence the administration of therapy.Â Keywords: touch and talk therapy, storytelling therapy and anxiety